Remodelling of Humeral Fracture in a Child with Osteopetrosis Tarda following Conservative Management - A 7-year Follow-up: A Case Report - Erkus, S (Malays Orthop J, 2019)
Osteopetrosis (OP) is a rare hereditary sclerosing bone dysplasia characterised by generalised hard and brittle bone secondary to defective osteoclastic function. Osteopetrotic bone is brittle, thus these subjects are prone to frequent fractures, particularly of the long bones. Due to defective osteoclastic function, remodeling is also defective in OP. This report is a case of humeral fracture in a 9 years old girl who was followed seven years. The fracture had remodeled totally similar to healthy bone at the final follow-up. Conservative treatment should be kept in mind in the management of fractures in children with OP, and fractures within acceptable angulations and/or translations should be treated conservatively without hesitation.